Development of Pediatric Surgery department in resource-limiting country - Mudassir Fiaz Gondal, Naeem Liaqat, Mudassir Fiaz Gondal, Naeem Liaqat (Journal of Rawalpindi Medical College, 2019)
Care of pediatric surgery patients demands a high level of commitment, expertise and logistic support as the child needs exclusive care from all aspects. At the same time, these services are neglected and not up to the mark, particularly in developing countries (1). It makes it compulsory to provide adequate and required infrastructure, equipment, trained staff and other logistics to take care of increasing burden of these patients. (1, 2) Pediatric surgery services are far lacking in Pakistan generally (1).As per American Pediatric Surgical Association, number of pediatric surgeons must be at least 1/100,000 population of 0-15 years (3). As per census of Pakistan done in 2017, the total population of 0-15 years was 43.4% of the total population (4). However, total pediatric surgeons working in Pakistan in 2019 were less than 200. The number of pediatric surgeons in Pakistan per 100,000 population is 0.26 (5), which is far less than the minimal required qualified consultants. Rawalpindi division is the fourth most populated city of Pakistan and has a population of 10.1 million as per census (6) and approximately 43.5 lacs are of the age 0-15 years.(4) Rawalpindi is a densely populated division of Punjab (6). Pediatric Surgery services are lacking in Pakistan generally, and in Northern Punjab especially. Enactment area of teaching hospitals of Rawalpindi includes a huge population of Northern areas of Punjab (including four districts of Rawalpindi), Khyber Pakhtunkhwa, Northern areas of Pakistan and Azad Jammu Kashmir. As only one public sector unit of pediatric surgery is available at federal level, so teaching hospitals of Rawalpindi have to provide care to a large population which reciprocates the burden exceeding the available resources. It results in provision of compromised care to the pediatric surgery patients. Developing pediatric surgery services at public sector hospitals is direly needed. Pediatric surgery department at Holy Family Hospital (HFH) started in July, 2016. Initially it started its services from a 4-bedded room and one day for Outpatient Department (OPD) patients. There was only one faculty member. However, later on, department progressed and soon teaching activities including rotation of post graduate residents (PGRs) was allowed. Afterwards in January 2018, this department got recognized for training of PGRs for FCPS program by the College of Physicians and Surgeons (CPSP) and Master of surgery program (MS) by University of Health Sciences (UHS), which populated the department. Currently pediatric surgery department, HFH is taking care of a huge number of patients presenting in OPD. It is providing its services in OPD for 3 days a week. The operation theatre services are being provided three days a week and 24/7 emergency cover for pediatric surgery cases is being provided. There are 4 faculty members now in pediatric surgery Department, HFH and 7 trainees of both FCPS and MS programs are being trained. Developing a pediatric surgery department at Rawalpindi Medical University (RMU) had been arduous. Pediatric surgery department cannot work alone, rather it is a team-based approach which needs exclusive support from pediatric medicine, anesthesia and intensive care units (ICU) staff (7, 8). Similar problems had been here as there was no trained staff for care of pediatric surgery patients, no faculty member from other units was there to join a newly developing department. However, luckily, pediatric surgery department found extensive support from the administration, general surgery, anesthesia and pediatric medicine departments which made it possible to develop a collaborative approach for these patients. Developing more and more departments is direly needed for provision of standardized and compassionate care to the patients regarding pediatric surgical services. It is need of the time to develop maternal and child health centres like Children hospitals so that multidisciplinary care may be available in a standardized fashion to children (1, 2). As the minimal invasive surgery services are developing globally, there is a need to develop these services at different centres of Pakistan. We suggest development of more centres and provision of logistic support to the newly developing departments in our country.